Clinical Brain Death with False Positive Radionuclide Cerebral Perfusion Scans - Sindhaghatta Venkatram; Sara Bughio; Gilda Diaz-Fuentes (Case Reports in Critical Care)
Practice guidelines from the American Academy of Neurology for the determination of brain death in adults define brain death as “the irreversible loss of function of the brain, including the brainstem.” Neurological determination of brain death is primarily based on clinical examination; if clinical criteria are met, a definitive confirmatory test is indicated. The apnea test remains the gold standard for confirmation. In patients with factors that confound the clinical determination or when apnea tests cannot safely be performed, an ancillary test is required to confirm brain death. Confirmatory ancillary tests for brain death include (a) tests of electrical activity (electroencephalography (EEG) and somatosensory evoked potentials) and (b) radiologic examinations of blood flow (contrast angiography, transcranial Doppler ultrasound (TCD), and radionuclide methods). Of these, however, radionuclide studies are used most commonly. Here we present data from two patients with a false positive Radionuclide Cerebral Perfusion Scan (RCPS).